Humanizing STEM education through student-faculty pedagogical partnerships - Cook-Sather, Alison; Salmeron, Diana; Smith, Theodore (Frontiers in Education, 2023)
STEM culture has consistently been characterized as exclusionary of a diversity of student identities, experiences, and voices. Through such exclusive and inequitable practices, STEM education can dehumanize. A growing body of scholarship documents ways in which student-faculty pedagogical partnership can support the creation of more equitable and inclusive practices. The research question we addressed is: How do faculty and student partners experience, perceive, and act on the potential of student-faculty pedagogical partnership to humanize STEM education? Combining aspects of a scoping review and reflexive thematic analysis, we analyzed 31 publications focused on pedagogical partnership in STEM in the arenas of learning, teaching, and assessment or curriculum design and pedagogic consultancy with student partners in the liminal role of pedagogical co-designer or consultant. Our review, informed by the experiences as well as the perspectives of the student co-authors, revealed five key findings about the aspects of pedagogical partnerships that contribute to humanizing STEM education. First, pedagogical partnerships give faculty access to students’ perspectives and humanity. Second, they support faculty in being, and being perceived as, more fully human. Third, they provide dedicated space and time to develop equitable approaches. Fourth, they support the enactment of equitable teaching. Fifth, they foster a sense of mattering, belonging, and agency in students. Drawing on these findings, we develop four recommendations for those interested in embracing partnership to humanize STEM education. The first is to create roles and support structures for facilitating genuine engagement across positions and perspectives. The second is to position underrepresented student partners to effect a culture shift. The third is to embrace non-STEM student partners’ contributions to humanizing STEM education. The fourth is to recognize this work as ongoing. Together, these findings and recommendations address calls to contribute to renewed and sustained attention to student experiences in relation to instructor values, dispositions, and positionalities. In addition, they reject harmful ideologies and practices that exclude a spectrum of identities, viewpoints, and values. Finally, they contribute to the creation of context-sensitive, inclusive, equitable, and empowering educational experiences for all students.